Antibacterial Activities of Ethanol Extracts Fruit Bodies of Ganoderma Lucidum and Rigidoporus Microphorus Against Escherichia Coli and Staphlyococcus Aureus - Noverita Noverita; Ritchie Y.H L.T (Universitas Nasional Jakarta, 2020)
Ganoderma lucidum and Rigidoporus microporus are two examples of macro fungi that are commonly found in forest areas in the highlands of Indonesia, and are even found in lowlands such as in urban forests in DKI Jakarta. Many of these macro fungi have been reported as potential medicinal substances, especially from the species G. lucidum, whose fruit bodies are usually obtained from forests in upland areas. The purpose of this study was to determine the antibacterial activity of the fungi G. lucidum and R. microporus obtained from several places in South Jakarta against the growth of E. coli and S. aureus bacteria. Testing for antibacterial activity was carried out using the Kirby-Bauer diffusion method. The results showed that the extract of G. lucidum fruit bodies was only able to inhibit the growth of S. aureus bacteria. While the fruit body extract of R. microporus was able to inhibit both types of tested bacteria (E. coli and S. aureus). The results showed that G. lucidum extract was only able to inhibit S. aureus bacteria. Meanwhile R. microporus extract was able to inhibit E.coli and S.aureus. There was no significant effect of increasing the concentration of mushroom fruit extract on the inhibition zone of the tested bacteria.